Dynamic Model for Hydro-Turbine Generator Units Based on a Database Method for Guide Bearings - Yong Xu; Zhaohui Li; Xide Lai (Shock and Vibration)
A suitable dynamic model of rotor system is of great significance not only for supplying knowledge of the fault mechanism, but also for assisting in machine health monitoring research. Many techniques have been developed for properly modeling the radial vibration of large hydro-turbine generator units. However, an applicable dynamic model has not yet been reported in literature due to the complexity of the boundary conditions and exciting forces. In this paper, a finite element (FE) rotor dynamic model of radial vibration taking account of operating conditions is proposed. A brief and practical database method is employed to model the guide bearing. Taking advantage of the method, rotating speed and bearing clearance can be considered in the model. A novel algorithm, which can take account of both transient and steady-state analysis, is proposed to solve the model. Dynamic response for rotor model of 125 MW hydro-turbine generator units in Gezhouba Power Station is simulated. Field data from Optimal Maintenance Information System for Hydro power plants (HOMIS) are analyzed compared with the simulation. Results illustrate the application value of the model in providing knowledge of the fault mechanism and in failure diagnosis.